PENGARUH GAMES ONLINE MOBILE LEGEND TERHADAP KESEHATAN MENTAL SISWA KELAS V DI SD NEGERI 106443 SEI BAHARU - Putri Junita; Layli Safitri; Syarifah Ainun Harahap (Pragmatik: Jurnal Ilmiah Ilmu Pendidikan, 2026)
This research aims 1) To determine the effect of the duration of playing mobile legend games on students' mental health. 2) To determine the negative impact that arises from addiction to playing mobile legend games on students' mental health. And 3) To find out students' social behavior that is influenced by the habit of playing mobile legend games. This type of research method uses quantitative methods with a correlational type. The data collection technique used by researchers is the scale method. The research results show that the results of the simultaneous F test analysis on the intensity of playing Mobile Legends games and sleep quality variables on mental health produce a significant influence. This is shown by the research results which obtained a significance value of 0.000 < 0.05, so that it can be stated that Ha3 in this study was accepted with an influence size of 13.4%.